Pengaruh Pemberian Metode 20-20-20 terhadap Penurunan Gejala Computer Vision Syndrome (CVS) - Gita Nurhikma; Dina Lusiana Setyowati; Iwan Muhamad Ramdan (Universitas Faletehan, 2022)
Computer Vision Syndrome (CVS) is a combination of problems or a set of symptoms in eyes due to activities of using digital devices such as computers, telephones, and tablets with near vision and lasts continuously for long periods. Employees who work on a computer for more than 2-4 hours a day is at risk of developing CVS which can affect their productivity at work. The purpose of this study was to determine the effects of giving 20-20-20 method on reducing CVS symptoms. The type of the research is true experiment with pretest-posttest control group design. The number of samples were 30 employees divided into the experimental group and the control group. The bivariate analysis used paired samples T-test for paired samples and independent samples T-test and Mann-Whitney test for non-paired samples with a significance level of 95% (α = 0.05). The results showed that there was a significant difference between CVS symptom score before and after the intervention with p value 0.001 (ρ<0.05). The researchers concluded that there was a significant effect of giving 20-20-20 method on reducing CVS symptoms of employees. Future researchers were expected to be able to innovate to reduce the symptoms of Computer Vision Syndrome (CVS).